Enhancing β-Carotene Concentration in Parental Lines of CO6 Maize Hybrid Through Marker-Assisted Backcross Breeding (MABB) - Natesan, Senthil; Duraisamy, Thirusenduraselvi; Pukalenthy, Bharathi; Chandran, Sarankumar; Nallathambi, Jagadeeshselvam; Adhimoolam, Karthikeyan; Manickam, Dhasarathan; Sampathrajan, Vellaikumar; Muniyandi, Samuel Jeberson; Meitei, Laishram Joykumar; Thirunavukkarasu, Nepolean; Kalipatty Nalliappan, Ganesan; et al. (Frontiers in Nutrition, 2020)
Vitamin A deficiency (VAD) is a global health problem, many people around the world, especially children and pregnant women are VAD deficient or insufficient. Maize is known as an important source of provitamin A for humans. Hence, enhancement of provitamin A carotenoids (pVAC) in maize varieties through breeding or biofortification is a better option for alleviating VAD in developing countries, especially India. So far, numerous maize hybrids developed in India. Among them, CO6 derived from UMI1200×UMI1230 is a popular maize hybrid and adopted to different agro-climatic zones of India, especially Tamil Nadu, Southern state of India. However, CO6 is deficient for pVAC carotenoid β-carotene. Thus, the objectives of this study were to increase the β-carotene concentration in UMI1200 and UMI1230 and generate the β-carotene enriched hybrids through marker-assisted backcross breeding (MABB). For this purpose, the maize genotype HP467-15 used as the donor for transferring the β-carotene gene, crtRB1 into UMI1200 and UMI1230. In the MABB scheme, we used one gene-specific marker (crtRB1 3′TE) and 214 simples sequence repeat (SSR) markers for foreground and background selection, respectively. As a result, six improved lines having recurrent parent genome recovery (RPGR) ranging from 90.24% to 92.42% along with good agronomic performance were generated. The β-carotene concentration of the improved lines ranged from 7.056µg/g to 9.232µg/g. Furthermore, five hybrid combinations were generated using improved lines and evaluated in comparative yield trial (CYT) and multi-location trials (MLT) along with original hybrid CO6 and commercial hybrids. It revealed that ACM-M13-002 was a superior hybrid with a 7.3 fold increase in β-carotene concentration over and comparable yield to CO6. In summary, the improved maize inbreds can be used as possible donors for the development of β-carotene-rich cultivars in maize breeding programs and β-carotene enriched hybrid developed in this study will hold great promise for food and nutritional security.